(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes translation theories that shed light on the general theory of translation. The authors call the described theories "specific translation theories." Specific examples from German and English illustrate the possibilities of applying these theories in translation practice. The authors came to the conclusion that the diversity of translation theories that have appeared in recent decades has created the need to systematize them. Special theories of translation have a purely practical nature, which is explained by different genres of translated texts.